Development of Digital Learning Materials to Foster Mutual Cooperation in Early Childhood through the Pancasila Student Profile Project - Melianti, Melianti; Syamsuardi, Syamsuardi; Herlina, Herlina; Hajerah, Hajerah (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Digital technology has increasingly become integrated into early childhood education, offering new opportunities to support learning and development. This study aimed to develop digital learning materials focused on the value of mutual cooperation as part of the Pancasila Student Profile Project (P5) in kindergarten. The research employed the ADDIE development model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The study involved 30 children aged 4-5 years and four teachers who facilitated the use of the digital materials. Data were collected through questionnaires, interviews, and observations. The validity test yielded a score of 2.87, classified as valid. Practicality analysis based on teacher response questionnaires reached 98.75%, indicating a strongly agree category. Effectiveness was assessed through childrens final performance, showing that the digital materials effectively instilled mutual cooperation values and increased children's engagement in digital-based learning. These findings suggest that the developed digital learning materials are a feasible and impactful resource for promoting character values and active participation in early childhood education.